Gantry Design and Fabrication for a Stationary Adaptive SPECT System - Richards, R. Garrett; May, Micaehla; Gardiner, Michael; Bechetti, Geno; Kalluri, Kesava S.; Auer, Benjamin; King, Michael A.; Kuo, Phillip H.; Furenlid, Lars R. (IEEE conference record - Nuclear Science Symposium & Medical Imaging Conference., 2021)
Additive tungsten manufacturing opens up new design possibilities for stationary single-photon-emission computed tomography (SPECT) systems. We are developing AdaptiSPECT-C: an adaptive SPECT system designed for clinical whole brain imaging with a focus on drug discovery research for neurodegenerative diseases. The design comprises a 24-stationary camera configuration with actively controlled adjustable multi-pinhole apertures. That is, each of the five pinholes assigned to a camera can be switched between three different aperture diameters, enabling successive acquisition of image data from the same subject with different tradeoffs between spatial resolution and sensitivity, with both multiplexed and non-multiplexed projections, in a single session.We present here the mechanical integration for AdaptiSPECT-C, including fabrication and construction of the gantry, modular camera assemblies with collimators, and lead shielding structures. AdaptiSPECT-C's cameras each have an 18 cm x 18 cm light collection area, arranged to point at a common 21 cm spherical field of view with 0.54 nominal magnification. A highly modular camera and semi-kinematic mounting design has been established and validated that allows for future system iterations with even more capable detectors and collimation strategies. By managing a balance of systems-level fabrication and assembly tolerances, AdaptiSPECT-C can be constructed efficiently without specialized expertise and is easy to service with a high degree of repeatability between successive camera installations.